Levetiracetam ameliorates ovarian function in streptozotocin-induced diabetic rats. (3rd August 2015) - Akman, Levent; Erbas, Oytun; Akdemir, Ali; Yavasoglu, Altug; Taskiran, Dilek; Kazandi, Mert
Abstract: Diabetes mellitus can adversely affect gonadal function. In the present study, we aimed to investigate the protective effects and mechanism of action of levetiracetam (LEV) on the ovaries in a streptozotocin (STZ)-induced diabetes model in rats. Twenty-one adult female rats were assigned to three groups as control, diabetes group treated with 1 mL/kg/d saline (STZ + SP) and diabetes group treated with 600 mg/kg/d LEV (STZ + LEV). Following 4 weeks treatment, blood samples were collected for biochemical analysis and ovariectomy was performed for histopathological examination. Plasma anti-Mullerian hormone (AMH), glutathione and total anti-oxidant capacity values were significantly lower whereas lipid peroxides and transforming growth factor-β (TGF-β) values were significantly higher in STZ + SP group compared to control. LEV treatment successfully decreased lipid peroxidation and TGF-β levels, and also increased anti-oxidant parameters and AMH levels in diabetic rats. Saline-treated rats significantly displayed ovarian degeneration and decreased counts of follicles. However, treatment of diabetic rats with LEV effectively prevented the degenerative changes and follicle loss. Also, LEV suppressed ovarian nuclear factor-kappa B (NF-kB) immunoexpression in diabetic rats. Taken together, we propose that LEV can ameliorate the adverse effects of diabetes on ovarian function via decreasing NF-kB expression and oxidative stress and increasing anti-oxidant status in rats. Chinese abstract: 糖尿病可对性腺功能产生不利影响。本研究中，我们旨在探讨左乙拉西坦（LEV）对链脲霉素（STZ）诱导的糖尿病大鼠卵巢的保护情况及其作用机制。我们将21只雌性成年大鼠随机分为控制组、1mL/kg/天生理盐水糖尿病治疗组（STZ+SP）和600mg/kg/天左乙拉西坦糖尿病治疗组（STZ+LEV）。四周后收集血液样本进行生化分析，切除卵巢进行病理组织学检查。与对照组相比，血浆抗苗勒管激素（AMH）、谷胱甘肽、总抗氧化活性值明显降低，而STZ+SP组脂质过氧化物、转化生长因子β（TGF-β）则明显升高。在糖尿病大鼠模型中，LEV治疗组显著降低了过氧化脂质和TGF-β水平，同时升高了抗氧化参数及AMH水平。生理盐水灌胃组大鼠模型中卵巢功能明显减退、卵泡计数明显减少。然而，接受LEV治疗的糖尿病大鼠模型有效地预防了大鼠卵巢功能的减退及卵泡数的损耗。同时，LEV也抑制了糖尿病大鼠卵巢核因子kB（NF-kB）的免疫性表达。综上，我们提出LEV可通过降低NF-kB表达和氧化应激反应，同时通过增加抗氧化状态来改善糖尿病大鼠的卵巢功能。